THE CLASSIFICATION OF HADITH ACCORDING TO THE SCHOLARS OF THE MADHHABS AND THE MUHADDITHUN (The Journal of Interdisciplinary Human Studies, 2026)
This article explores how scholars of the Islamic legal schools (madhhabs) and the muhaddithun classified hadith, analyzing the conceptual foundations and criteria that underpinned their respective systems of classification. It examines key categories such as mutawatir and ahad reports, as well as the gradations of authenticity sahih, hasan, and daʿif highlighting the methodological nuances in their evaluation. The study further investigates the distinctive approaches adopted by jurists (fuqahaʾ) and hadith specialists in utilizing hadith as a source of legal and doctrinal authority, with particular attention to the acceptance of solitary reports, the role of contextual indicators (qaraʾin), and the reconciliation of apparently conflicting narrations. By offering a comparative analysis, the article demonstrates both the areas of convergence and divergence between these scholarly traditions, thereby contributing to a more comprehensive understanding of hadith epistemology and its application in Islamic legal theory.
Keywords: Companion (Sahabi); Tabiʿun; Tabaʿ al-Tabiʿin; Mutawatir